(untitled) (Desenvolvimento em Questão, 2020)
The objective of this research is to analyze the degree of adherence to transparency requirements and access to information in the electronic portals of the state-owned companies belonging to the states of Rio Grande do Sul (RS), Paraná (PR) and Santa Catarina (SC). From a qualitative, descriptive and documentary research, it was possible to show that the state-owned PR companies achieved 76% adherence to transparency, followed by RS and SC state, with 64% and 62%, respectively. Still, 68% of the sample meets the requirements required for electronic sites, being classified as medium degree of adhesion. However, there is still no full adherence, nor even a high degree of adherence to all the analyzed indicators, demonstrating that the supervision of electronic portals needs to be more effective.